Making Some Sense of the Constitutional Family - Katharine K. Baker (Washington University Journal of Law and Policy, 2023)
This essay explores the Supreme Court’s approaches to family definition. It unpacks how the Court has defined family differently in different contexts, and it argues that what can appear to be a confused doctrine actually makes some sense once one realizes that how the Court defines family is related to why the State is recognizing family at all. When the law recognizes family for any purpose, it must define it, either with reference to some extra-legal determinant like genetics, a pure legal construction like marriage, or a case-by-case assessment of lived experience like function. The Court has relied on all three of these mechanisms to define family, but it has almost never explained why it uses different definitions at different times. This essay examines the Court’s jurisprudence and begins to address the question of why it has used different definitions of family in different contexts. While much of the Court’s reasoning in these cases either never made sense or no longer makes sense given the evolution of technology and social norms, many of the Supreme Court’s seemingly confused results can be justified if one takes time to appreciate the different contexts in which the State has defined family.
Keywords: Family; Marriage; Supreme Court; Constitutional Law